Montaje de un sistema de medición de variables eléctricas para las instalaciones de generación de energía solar fotovoltaica en la universidad Antonio Nariño sede Cúcuta - Vargas Vargas, John Freddy (Universidad Antonio Nariño, 2021)
The degree work is oriented to the assembly of an electrical variables measurement system with Arduino technology in photovoltaic solar power generation facilities at the Antonio Nariño University, Cúcuta headquarters. Currently, the students of the Universidad Antonio Nariño, Cúcuta headquarters have a cultural interaction and constant work in relation to renewable energies due to the development of several degree projects that have been implemented at the headquarters with respect to this type of energy, which They have made the student aware of the current global and national environmental crisis, since there is a high percentage of energy extracted from fossil fuels, water sources and nuclear energy, which high high the environment. This leads us to reflect on the importance of creating laboratories for the student to manipulate renewable energy first-hand and lead him to contemplate the development of designs and applications of renewable energy in industry and the daily life of our homes, taking into account Note that Colombia, due to its geographical position, is a privileged country for the development of this type of energy. The assembly of the system focuses on finding the best laboratory in terms of cutting-edge technology and low construction costs, based on a mathematical model that allows the student to carry out continuous learning about the design, application, control and measurement of electrical variables. involved in photovoltaic solar energy systems.